Neferine, a natural alkaloid from Nelumbo nucifera, ameliorates experimental chronic ulcerative colitis in mice - Xiangjing Min; Yishan Zhou; Shuangli Xiang; Rong Sun; Qin Wu; Jingshan Shi; Xiuping Chen (Elsevier, 2021)
Objective: Ulcerative colitis (UC), a chronic inflammatory disease, is closely associated with the development of colorectal cancer. Neferine is a natural alkaloid that possesses many therapeutic effects. Our previous studies showed that neferine showed a significant protective effect on the acute ulcerative colitis mouse model. Here, the protective role of neferine on chronic UC was investigated. Methods: A chronic mice UC model was established by employing dextran sodium sulfate (DSS) and neferine was orally administrated. The disease activity index (DAI) scores were calculated. The levels of pro-inflammatory mediators were determined by ELISA kits. The pathological changes were evaluated by H&E staining. Protein expressions were detected by immunohistochemistry and Western blotting. Results: Neferine treatment significantly decreased the DAI scores, ameliorated pathological injuries, and reduced the levels of myeloperoxidase (MPO), IL-1β, IL-6, and TNF-α. Furthermore, the expressions of NF-κB p65, receptor-interacting protein kinase 1 and 3 (RIP1 and RIP3), intercellular adhesion molecule-1 (ICAM-1), and vascular cell adhesion molecule-1 (VCAM-1) in colon tissues were suppressed by neferine. In addition, the decreased expression of caspase-8 and IκBα were restored by neferine. Conclusion: Neferine protects chronic UC by regulating the secretion of pro-inflammatory cytokines and inhibiting the NF-κB signaling pathway.